2016
DOI: 10.1016/j.jdiacomp.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Polyol accumulation in muscle and liver in a mouse model of type 2 diabetes

Abstract: Aims Type 2 diabetes (T2D) is a complex metabolic disease leading to complications in multiple organs. Diabetic myopathy and liver disease are common complications of T2D, but are incompletely understood. To gain insight into the pathogenesis of these conditions we performed metabolomic analysis of skeletal muscle and liver in a mouse model of T2D. Methods Tissue metabolomics were performed by GC/MS and LC/MS of the skeletal muscle and liver in the MKR mouse model of T2D, compared with control mice. MKR mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A reduction in available NADPH, due to the overutilization of the Polyol Pathway, significantly decreases GSH levels and thus limits the ROS-scavenging activity of GSH, and further increases ROS levels [14]. A diabetic mouse model (MKR) vs. control study performed in 2010 revealed sorbitol levels 2.5 times higher in MKR when compared to a control Also found was 1.7 times lower levels of the reduced glutathione (rGSH) in skeletal muscle [15]. Therefore, it is understood that the overutilization of the polyol pathway due to glucose excess is a major source of oxidative stress, by limiting the recycling of GSH via GSR induced by diabetes.…”
Section: Pathogenesis In T2dmmentioning
confidence: 99%
“…A reduction in available NADPH, due to the overutilization of the Polyol Pathway, significantly decreases GSH levels and thus limits the ROS-scavenging activity of GSH, and further increases ROS levels [14]. A diabetic mouse model (MKR) vs. control study performed in 2010 revealed sorbitol levels 2.5 times higher in MKR when compared to a control Also found was 1.7 times lower levels of the reduced glutathione (rGSH) in skeletal muscle [15]. Therefore, it is understood that the overutilization of the polyol pathway due to glucose excess is a major source of oxidative stress, by limiting the recycling of GSH via GSR induced by diabetes.…”
Section: Pathogenesis In T2dmmentioning
confidence: 99%
“…During this course of non-diffusive behavior of sorbitol, intra-cellular accumulation of sorbitol initiates, leading to occurrences of osmotic stress [67,116]. Further, with the exhaustive analysis of early studies it was revealed that sorbitol is converted to fructose via sorbitol dehydrogenase, with NAD+ getting reduced to NADH.…”
Section: Retinopathy and Candidate Genesmentioning
confidence: 99%
“…Subsequently, sorbitol may convert to fructose by sorbitol dehydrogenase [77]. A similar spill-over effect of glycolysis has been established as an ancillary pathway in type 2 diabetes mellitus [77][78][79][80]. Increased activity of the polyol pathway was also reported in other liver diseases such as Wilson's disease that is characterized by copper accumulation in the liver and other organs [81].…”
Section: Discussionmentioning
confidence: 75%